Selection of Silvicultural Techniques - Ranganathan, C. R. (Indian Forester, 1950)
As a reflex of the continental range of climatic conditions prevailing in India, the forests in the country exhibit a corresponding diversity of types. While extensive coniferous forests occur on the Himalayas and tropical evergreen forests in wet localities, the mass of India's forests belongs to the tropical deciduous type characterized by a great wealth of species, of which only a few are valuable. The sal forests of Northern India are an important exception in that the species occurs gregariously as the climax dominant over extensive tracts. High forest systems of natural regeneration have been successful only in the coniferous forests on the Himalayas and in sal forests where advance growth is already present in quantity. It has not been found possible to rely on natural reproduction for restocking gaps left after selection fellings in mixed forests. The effect of such fellings is in general to increase the proportion of valueless species at the expense of the valuable ones. This applies in particular to teak forests, where the species occurs in mixture with other less valuable or useless species. The problem of regenerating such forests has been solved by making compensatory plantations of the selected species in suitable sites in the forest. Our fuel forests are worked under the Coppice System but repeated working has been found to lead to reduced density of the crop and to lower yields. This effect has had to be countered by special measures of artificial regeneration. For these various reasons India has had to develop special techniques of artificial regeneration of which the most significant are (1) the controlled use of fire in regeneration areas, (2) the rob method, (3) Taungya method and (4) the method of stump planting. A brief descripion of. these methods is given. New developments in the utilization of timber and the programme of afforestation which has been decided on in the country for increasing our timber and firewood potential and for securing a more balanced distribution of forests will alike call for research aiming at advances and modifications in our silvicultural techniques to meet new requirements. The importance of statistical control of silvicultural research has been realized in India and progressive steps have been taken during the last two decades at the Forest Research Institute for securing such control.